PARTICIPATION IN ISLAMIC CRIMINAL LAW: PRINCIPLES OF LAW AND JUSTICE - Marpaung, Zaid Alfauza (Program Pascasarjana UIN Sumatera Utara Medan, 2024)
This research aims to analyze the mechanism of inclusion in Islamic Criminal Law, with a focus on historical and contemporary aspects. Islamic Criminal Law has unique characteristics that differentiate it from other legal systems, especially in terms of implementing sanctions and justice. In this context, participation in criminal acts is divided into direct and indirect involvement, each of which has different legal consequences. Apart from that, this research also highlights the relevance of the principles of justice in Islamic Criminal Law in the modern era, as well as the challenges faced in their implementation. Thus, it is hoped that this research can contribute to the development of a more just and civili ed Islamic Criminal Law.